Spectrum of presentation and prognostic factors in non-traumatic small bowel perforations - Yadav, Anoop; Kumar, Satish; Marwah, Sanjay; Argal, Narottam S.; Yadav, Chander M.; A., Sethu R. P.; Singh, Anamika; Bhardwaj, Madan Gopal (International Surgery Journal, 2021)
Background: The small bowel perforation peritonitis is one of the main causes of generalized acute peritonitis in developing countries.The aim is to find out the prognostic factors affecting the mortality and morbidity of non-traumatic small bowel perforations. Methods: A total of 50 patients of any age and either gender of non-traumatic small bowel perforation peritonitis were included and studied prospectively. The prognostic evaluation was assessed by the impact of pre-operative prognostic factors and per operative findings on post-operative complications and mortality. Results: One third of the patients were of 20-30 years of age followed by 18% who belonged to 10-20 years age group. Operative findings revealed mean duration of surgery was 2 hours. Majority of patients (33) had bilio-purulent peritonitis. Post-operative pulmonary complication revealed 56% (28 out of 50) patients were having pulmonary complications. Post-operative wound complication showed surgical site infection as the most common complication noted and managed by sending wound culture and changing antibiotics. Second most common was burst abdomen managed initially by dressing and thereafter secondary wound closure. Delay in intervention (DII) had significant correlation with world society of emergency surgery (WSES) score and amount of peritoneal fluid. Conclusions: Most common cause of non-traumatic small bowel perforation was typhoid ileal perforation with most common presentation being pain abdomen. The significant factors defining the outcome of these patients were volume of intra-peritoneal fluid (purulent/fecal) >1000 ml, WSES score >6 and Mannheim’s peritonitis index (MPI)>18.